Stress distribution and displacement in the maxillofacial complex during intrusion and distalization of the maxillary arch using miniplates versus mini-implants: a 3-dimensional finite element study - Abinaya Somaskandhan; N M. Vijay Kumar; R. Devaki Vijayalakshmi (Progress in Orthodontics, 2023)
Abstract Objectives To three-dimensionally analyse the stress distribution and displacement pattern in the maxillofacial complex following intrusion and distalization of the maxillary arch using finite element analysis in skeletal class II malocclusion with prognathic maxilla and vertical maxillary excess using miniplates and mini-implants. Materials and methods Finite Element models of a skull, Y-shaped stainless steel miniplate, mini-implant and a posted arch were generated. Three force levels (1) 200 g (2) 300 g and (3) 500 g per side were applied to the assembly. The models were pre-processed and the analysis was performed using ANSYS version 18.1 software. Alterations in von mises stress, principal maximum stress, principal minimum stress and compressive stress were analysed around the sutures and surface landmarks. Results With miniplates, there was a maximum stress concentration at the zygomatic buttress with even stress distribution at the fronto-maxillary, zygomatico-temporal, zygomatico-frontal and pterygomaxillary sutures along with anatomical landmarks such as frontal process of maxilla, ANS, Point A, prosthion and maxillary process of zygoma. First molars experienced greater distalization effects with buccal flaring when miniplates were used. With mini-implants, canine and premolars also exhibited greater distalization effects. In the root apices, lateral incisors showed increased lingual root movement with mini-implants. Conclusion Miniplates provide a greater distalizing effect while mini-implants produce increased intrusive effect. The distalizing effect is greater when 500 g of force is applied using miniplates with significantly even stress distribution and displacement pattern.